Evaluation of Cone-beam Computed Tomography to differentiate Odontogenic Periapical Cysts and Granulomas (Journal of National Institute of Neurosciences Bangladesh, 2023)
Background: Cone-beam Computed Tomography is a useful diagnostic tools for the detection of odontogenic peripheral cysts and granulomas.Objective: The purpose of the present study was to assess the accuracy of CBCT for diagnosing periapical cyst and granuloma.Methodology: This cross-sectional study was conducted from February 2017 to November 2017. Following inclusion and exclusion criteria consecutive patients who were consult in the department of oral and maxillofacial surgery of Dhaka Dental College Hospital and Bangabandhu Seikh Mujib Medical University for periapical infection was selected. Only those patients showing a periapical lesion of minimum 5 mm size was included in the study subject. Intra-oral periapical radiograph showing criteria was presence of apical radiolucency of 5 mm, corticated borders and displacements of roots. The CBCT images were done for those patients. The following features were documented on CBCT like location at the apex of involved tooth, well defined corticated border, shape is curved or circular, internal structure of lesion is radiolucent, displacement and resorption of the roots of adjacent teeth with a curved outline and perforation of cortical plate. Histopathological specimens were obtained for microscopic examination. The findings of histopathological examinations were correlated with the findings of CBCT.Results: Out of 50 subjects, 41(82.0%) subjects were diagnosed as cyst and 9(18.0%) subjects were as granuloma. Postoperative histopathology revealed 37 out of 41 were cysts and 4 were granulomas. Out of 9 granulomas 3 were cysts and 6 were granulomas. In this study we found the PPV 90.2439 and NPV 66.66. Diagnostic Accuracy was measured by calculating TP, TN and total population. The accuracy was 86%.Conclusion: In conclusion Cone-beam Computed Tomography has high accuracy of CBCT for diagnosing periapical cyst and granuloma.Journal of National Institute of Neurosciences Bangladesh, July 2022;8(2):171-174